CONGENITAL TOXOPLASMOSIS: CLINICAL COURSE AND RESIDUAL OUTCOMES - L. Yu. Barycheva; M. V. Golubeva; M. A. Kabulova; I. V. Kostornaya (Детские инфекции (Москва))
We examined 69 infants with clinically manifested forms of congenital toxoplasmosis diagnosed in theStavropolregion in the period from 1992 to 2012. The clinical course was characterized by a predominance of severe forms of congenial toxoplasmosis, high mortality rate (39,1%), predominant damage the central nervous system (100%) and adverse neurological outcome. Surviving children developed disabilities at the outcome of congenital toxoplasmosis such as hydrocephaly (71,4%), microcephaly (9,5%), cerebral palsy (52,4%), episindroma (16,7%), mental retardation (19,0 %) complete or partial blindness (28,6%).